Eagerness of Slum Children Study in Primary Schools: A Study of Guwahati Urban Slum Area (Islampur) of Assam, India (International Journal of Food and Nutritional Sciences, 2022)
The objective of the Study is to find out the study of the Eagerness of Slum Children study in Primary Schools of Guwahati Urban Slums area (Islampur), Assam. Descriptive Survey Method was adopted and Fifty (50) slums Children (age group 6-14 years) of Guwahati Urban Slums area (Islampur) were used as sample where self prepare Questionnaire, Interview and Observation Method were used as tools for study. The data were analyzed in Percentage Method and Bar Diagram. The finding of study were 68.3% of children attend school to learn 3R’s ,76.4% for better job in future, 55.5% to become independent in future,63.2% for development of Self esteem, 86.3% for Mid-Day Meal, 45.8% for loving School Environment and 40.3% to play with friends. Suggestions of the study were the schools should be supervised regularly Slum Children and Volunteer Programs should organize which are an effective tool for ensuring access to education for the children living in slums. Parents and Teachers should talk to them in a positive tone, and inquire about their well-being and suggest them.